Sociabilidad virtual y criterios de selección en mujeres y varones heterosexuales - Palumbo, Mariana (CIICLA, Universidad de Costa Rica, 2019)
This article problematizes the notion of sociability in the context of late modernity and analyzes how the selection criteria operate in adult cisheterosexual men and women of middle sectors, resident in the Metropolitan Area of Buenos Aires (Argentina), when they seek erotic and / or affective encounters in spaces of virtual sociability. This second objective focuses on social class and lifestyle. The methodology of the article is qualitative: 150 profiles of websites and dating applications (Match, Badoo, Tinder, and Happn) were studied and 30 in-depth interviews were conducted with cis women and men, who use those websites and applications. Among the results it is highlighted that, in the design of the profiles, the images used are those on leisure and comfort (scenarios of paradisiacal beaches or European landscapes, sparkling drinks, and nautical activities) and also those related to work and education.